2014
DOI: 10.5114/wiitm.2014.44056
|View full text |Cite
|
Sign up to set email alerts
|

The use of thermography to design tissue flaps - experimental studies on animals.

Abstract: IntroductionMethods allowing one to locate the position of a cutaneous perforator do not allow one to determine the boundaries of the vascularized skin. In clinical practice this causes complications in the form of marginal necrosis of the flap.AimTo examine the usefulness of thermography to assess the extent of vascularization of the skin and subcutaneous tissue by a single perforator.Material and methodsThirty-one male rats were used. Using dynamic thermography the perforators on the abdominal skin were loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A review by John et al [83] reported that IRT can identify hyperthermic events and indicate the loss of local circulation (ischemia), so it can serve as an indicator in the field of reconstructive plastic surgery by distinguishing viable from non-viable tissues. For example, Czapla et al [84], used 31 rats as models for skin tissue flaps. IRT analysis showed that the flaps' frequency of ischemia and partial necrosis showed significant differences (P = 0.024) that were attributed to changes in dermal circulatory patterns.…”
Section: Monitoring Of Non-visible Injuriesmentioning
confidence: 99%
“…A review by John et al [83] reported that IRT can identify hyperthermic events and indicate the loss of local circulation (ischemia), so it can serve as an indicator in the field of reconstructive plastic surgery by distinguishing viable from non-viable tissues. For example, Czapla et al [84], used 31 rats as models for skin tissue flaps. IRT analysis showed that the flaps' frequency of ischemia and partial necrosis showed significant differences (P = 0.024) that were attributed to changes in dermal circulatory patterns.…”
Section: Monitoring Of Non-visible Injuriesmentioning
confidence: 99%
“…On POD 3 and POD 7, the average temperature in the necrotic area did not significantly differ from the total flap area, likely due to the influence of core body temperature (Table 1). Since rats have minimal dorsal fat tissue, the skin flap is in direct contact with the body core, which affects the temperature distribution [35]. This core temperature effect minimized the temperature gradient between necrotic and non-necrotic areas, making the impact of external factors more prominent.…”
Section: Discussionmentioning
confidence: 99%
“…Then, 24 h after flap placement, the correct blood flow through perforators was assessed with IRT and macroscopical (necropsy) observations. Necrosis occurred in places where IRT did not detect perforators in 12 of 31 cases [ 80 ].…”
Section: Thermal Imaging Applied To Assess Tissular Damage Degree And...mentioning
confidence: 99%